PENDUDUK POLITIK PADA PEMILIHAN GUBERNUR PROPINSI DAERAH KHUSUS IBU KOTA JAKARTA 2017: Dinamika Data Pemilih Putaran Pertama dan Putaran Kedua - Rahmatulloh Rahmatulloh (Jurnal Ilmiah Mimbar Demokrasi, 2017)
This Study is to describe the updating of voters data used in the 2017 Gubernatorial and Vice Governor Election both in the first and second rounds. Description begins from the residence data of the Ministry of Home Affairs in the form of DP4 submitted to the KPU to be updated and the final result becomes DPT. The problem of voters data arises regarding the certainty of population data that has not fully reached the development of the population due to the limitations so that the voters use the proof of residence in the form of Electronic ID and Suket in DPTb for voting in TPS. The result of data voters local election in DKI 2017 accuracy level still not according to public expectation.